Simulasi Konveyor Penghitung Barang Berbasis PLC-HMI Sebagai Media Pembelajaran - Rizki Faulianur; Mhd Ridho Pratama; Mahmud (Politeknik Aceh, 2023)
As time goes by, learning media in educational institutions need to be innovated according to industry demand through curriculum development mechanisms. One of the learning media that will be developed is the Programmable Logic Controller (PLC) and Human Machine Interface (HMI) which will interact in the PLC course. HMI is a device that connects humans with working machines displaying visualization of input output equipment connected to a PLC. This research aims to create a PLC HMI-based goods counter conveyor simulation as a learning medium in the Aceh Polytechnic Mechatronics Study Program. The results obtained were that learning media was successfully created with PLC and HMI indications that could communicate to simulate goods counting conveyors. In this module there is an average delay of 2 seconds which is caused by the unresponsive response of the HMI touchscreen. However, overall this module is quite reliable and has been applied to increase competency in PLC courses.